2016
DOI: 10.1016/j.juro.2016.05.105
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Gleason 3 + 5 = 8 Prostate Cancer Diagnosed on Needle Biopsy: Prognostic Comparison with Gleason 4 + 4 = 8

Abstract: Using the most current standards of prostate cancer grading the prognosis is not different in Gleason score 3 + 5 = 8 and 4 + 4 = 8 cancers. This justifies including both in Grade Group 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 14 publications
4
33
0
Order By: Relevance
“…For instance, we noted in our cohort that men with GG4 disease without CR/IDC had DSS rates comparable [ 5 1 _ T D $ D I F F ] to those with GG2 and GG3 disease. This is in line with the findings of Harding-Jackson et al [ 5 2 _ T D $ D I F F ] [27], who also found relatively good outcome in GG4 Pca patients without cribriform pattern. With the introduction of the GG system, all patients with GS8 are classified as GG4 Pca patients irrespective of the GS being 3 + 5, 4 + 4, or 5 + 3.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…For instance, we noted in our cohort that men with GG4 disease without CR/IDC had DSS rates comparable [ 5 1 _ T D $ D I F F ] to those with GG2 and GG3 disease. This is in line with the findings of Harding-Jackson et al [ 5 2 _ T D $ D I F F ] [27], who also found relatively good outcome in GG4 Pca patients without cribriform pattern. With the introduction of the GG system, all patients with GS8 are classified as GG4 Pca patients irrespective of the GS being 3 + 5, 4 + 4, or 5 + 3.…”
Section: Discussionsupporting
confidence: 92%
“…With the introduction of the GG system, all patients with GS8 are classified as GG4 Pca patients irrespective of the GS being 3 + 5, 4 + 4, or 5 + 3. Van den Bergh et al found that men with GS 3 + 5 = 8 had significantly better BCRFS than GS8 patients with any of the other grade combinations, although such a difference could not be confirmed by others [ 5 3 _ T D $ D I F F ] [26][27][28]. Detailed analyses for the presence of CR/IDC in this heterogeneous population of GG4 Pca patients might further improve Pca grading.…”
Section: Discussionmentioning
confidence: 80%
“…74 Notably, among Gleason score 8 cancers, the question of whether the highest Gleason grade was 3 + 5 versus 4 + 4 proved only mildly predictive of recurrence. However, the presence of cribriform cancer dichotomised cancer-specific survival in Gleason 8 cancer, 75 corroborating another large biopsy-based study showing that across all Gleason score >6 carcinomas, the presence of a cribriform pattern predicted metastatic disease and death of disease. 63 Together, these studies indicate that cribriform architecture in prostate cancer carries a much higher risk of disease progression compared to the other Gleason grade 4 patterns.…”
Section: Glomeruloid Architecturesupporting
confidence: 76%
“…The consensus grade differed from the initial grading of the case by the submitting pathologist in only three cases (one with higher consensus grade and two with lower grades). Among the seven cases listed as Other grade (Table ), one case of GS 2 + 3 = 5 and six cases of GS 3 + 5 = 8 were grouped with ISUP 1 and 4, respectively, for further analysis; however, this did not alter any of the consensus decisions.…”
Section: Resultsmentioning
confidence: 99%